Penggunaan Media Sosial sebagai Sarana Advokasi: Studi Kasus Kelompok Disabilitas Kabupaten Jember - Sukron Makmun; Rohim Rohim; Fadillah Endah Sunarsiyani (Politicos: Jurnal Politik Dan Pemerintahan, 2021)
This study aims to reveal the efforts of disability groups in Jember Regency to show their existence through social media. This type of research is descriptive qualitative with data sources from observations, interviews, and literature studies. The results of the study indicate that the subordination of people with disabilities as persons with special needs is integrated with the culture of the community. Social media is a choice of space where the existence of disabilities is connected to each other. Social media offers values, new paradigms to raise various issues of lifestyle, joint effort, personal creativity and conditions related to the public sphere. The selection of candidates for district heads from persons with disabilities has shown the existence of disability groups present in a practical political framework as well as changing societal stereotypes.